2, 2'-bipyridine as a masking agent of ruthenium in the PUREX process. Issue 10 (3rd July 2021) - Thevenet, Alexiane; Marie, Cecile; Tamain, Christelle; Guilbaud, Philippe
ABSTRACT: The extraction of ruthenium by tri- n -butyl phosphate (TBP) is an issue for the PUREX process. The addition of 50 mM of 2, 2ʹ-bipyridine (BIPY) reveals that ruthenium can be maintained in 3 M HNO3 aqueous solution after heating at 90°C for 4 hours. The Ru-BIPY complex was characterized using UV-Visible and Raman spectroscopies, and single crystal X-Ray diffraction. These technics are in agreement with a 1:2 complex formation in HNO3 medium. The selectivity toward uranium was studied by solvent extraction experiments: the BIPY ligand is still able to maintain ruthenium in the aqueous phase whereas uranium is still extracted.